(untitled) (American Journal of Technology and Applied Sciences, 2023)
The topic of conversion translation transposition interpretation in various contexts is the focus of this article. Language units in conversion relations are examined from a variety of angles, and their unique characteristics are discussed. The relationship between conversion transformations and other modifications is examined in the article. Additionally, the impact of intricate translation modifications on conveying the original text’s discursive structure in the translation is taken into account.